Disseminated Intravascular Coagulation (DIC) akibat gigitan ular: laporan kasus - Ni Komang Krisnawati; Ida Ayu Putri Wirawati; Sianny Herawati; Ni Nyoman Mahartini; Anak Agung Ayu Lydia Prawita; Ekarini Katharina Yunarti Nabu (Intisari Sains Medis, 2021)
Background: Snakebite cases are cases of emergency that are often found in the Emergency Unit, especially in rice fields, forests, plantations and swamps. There is no definitive data on the number of snakebite cases in Indonesia. Morbidity and mortality of snakebite cases are highly dependent on the type of snake species, the number and type of can that enter the body, as well as the availability of anti-snake serum.In these patients were found Disseminated Intravascular Coagulation (DIC) due to snake bites.Case Presentation: A 5-years female patient complained of pain in the right hand due to snakebite about 30 minutes before entering the hospital. The snake is green with a red tail, a triangular head shape and a length of about 30 centimeters, biting the middle finger of the patient's right hand. Swollen redness and pain are felt spreading to the shoulders. Physical examination of compos mentis patients with a pulse rate of 96 times per minute, breath rate of 20 times per minute and temperature of 36.7oC. There was found edema and bullae in digiti III in the right manus region, palpably warm, and there is press pain. In the antebrachial region to the right humerus also found the presence of edema and press pain. Patients with normochromic normositer anemia with thrombocytopenia as well as lengthening of coagulation physiology decreased fibrinogen and increased D-dimer.Conclusion: Snake venom can be hemotoxic, neurotoxic and cytotoxic. Snakebite cases require rapid and comprehensive management to minimize the possibility of disability and death.  Latar Belakang: Kasus gigitan ular merupakan kasus kegawatan yang sering dijumpai di Unit Gawat Darurat terutama di daerah area persawahan, hutan, perkebunan dan rawa. Tidak ada data yang pasti mengenai jumlah kasus gigitan ular di Indonesia. Morbiditas dan mortalitas kasus gigitan ular sangat tergantung dari jenis spesies ular, jumlah dan jenis bisa yang masuk ke dalam tubuh serta ketersediaan serum anti bisa ular.Presentasi Kasus: Pada pasien ini ditemukan Disseminated Intravascular Coagulation (DIC) akibat gigitan ular. Pasien perempuan, usia 5 tahun dengan keluhan nyeri pada tangan kanan akibat gigitan ular sejak sekitar 30 menit sebelum masuk rumah sakit. Ular berwarna hijau dengan ekor merah, bentuk kepala segitiga dan panjang sekitar 30 centimeter, menggigit jari tengah tangan kanan pasien. Bengkak kemerahan dan nyeri dirasakan menjalar sampai ke bahu. Pemeriksaan fisik pasien compos mentis dengan laju nadi 96 kali per menit, laju nafas 20 kali per menit dan suhu 36,7oC. Pada regio manus kanan ditemukan adanya edema dan bullae pada digiti III, teraba hangat dan terdapat nyeri tekan. Pada region antebrachii sampai humerus kanan juga ditemukan adanya edema dan nyeri tekan. Pasien mengalami anemia normokromik normositer dengan trombositopenia serta pemanjangan faal koagulasi, penurunan fibrinogen dan peningkatan D-dimer.Kesimpulan: Bisa ular dapat bersifat hemotoksik, neurotoksik dan sitotoksik. Kasus gigitan ular memerlukan penatalaksanaan yang cepat dan komprehensif sehingga dapat meminimalkan kemungkinan kecacatan dan kematian.